ANALYSIS OF CUSTOMER RELATIONSHIP MANAGEMENT (CRM) INFLUENCE ON SATISFACTION AND ITS IMPACT ON CONSUMER LOYALTY OF PT. RAHARJA DUTA SOLUSINDO - Ratih Dewi Sumantri; Moch. Mukti Ali; Arissetyanto Nugroho (Dinasti International Journal of Education Management And Social Science, 2020)
The purpose of this study was to study the Analysis of the Influence of Customer Relationship Management (CRM) on Satisfaction and Its Impact on Customer Loyalty of PT. Raharja Duta Solusindo by measuring indicators that influence the Customer Relationship Management (CRM) variable, Customer Satisfaction and Loyalty. This research uses descriptive research design using survey methods. Sampling uses certain criteria where respondents have attended at least 1 training at PT. Raharja Duta Solusindo as a sampling technique. This study discusses using structural equation modeling (SEM) - Lisrel to discuss the significance of the relationship of the overall model and predetermined pathway. The findings show that the variable Customer Relationship Management (CRM) shows a positive and significant impact on Satisfaction, Customer Relationship Management (CRM) has a positive and significant effect on Customer Loyalty and customer satisfaction shows positive and significant impact on customer loyalty.